Development of native Pseudomonas aeruginosa bioformulations with plant growth promoting potential for apple crop in Himachal Pradesh. (10th February 2022) - Sharma, Ranjna; Sharma, Subhash
Abstract: This study was conducted to characterize different plant growth promoting Pseudomonas strains isolated from wet temperate zones of Himachal Pradesh and two best effective plant growth promoting P. aeruginosa strains An-14-Mg and An-15-Mg were tested under field conditions to evaluate their growth promotional effect on apple crop. Maximum production of all the plant growth promoting traits were shown by two Pseudomonas isolate An-14-Mg and An-15-Mg. Maximum phosphate solubilization was shown by An-15-Mg (46 mm) whereas highest siderophore units (SU) were recorded in An-14-Mg (71.23%SU) followed by An-15-Mg (70.12%SU) which were statistically at par with each other. Highest IAA production (95 µg/ml), HCN (++++) and ammonia (++++) production was observed again in Pseudomonas isolate An-15-Mg. Both the strains exhibited 99% level of similarity with P. aeruginosa . The presence of An-14-Mg, An-15-Mg alone and consortium were tested under field conditions to study their effect on percent survival of apple rootstocks, plant height and number of shoots up to 3 years period. Maximum increase in percent survival, plant height, number of shoots, chlorophyll content and available NPK content of soil were observed in consortial bioformulation after 3 years growth observed in apple plants. Both the P. aeruginosa strains were reported first time as plant growth promoter with apple tree, therefore can be used as biofertilizer in apple crop of Himachal Pradesh.